Dampak Variabel Makro Ekonomi Domestik dan Global Terhadap Indeks Saham Syariah Indonesia (ISSI) Periode Mei 2011–Mei 2019 - Fitri Rahmawati; Nirmala Baini (Institut Agama Islam Negeri Kendari, 2019)
This study aims to find out empirically the effect of macroeconomics variables on the movements of the Indonesian Islamic Stock Index (ISSI). This research uses quantitative research methods, using multiple linear regression analysis models. Data collection uses secondary data from documentation related data. Data is taken from the monthly closing price of each variable from May 2011 to May 2019. The research test uses the t test and F test and is processed using Eviews8. The results showed that BI Rate and Exchange Rates (Kurs) has a negative and signifcant impact on Indonesia Sharia Stock Index (ISSI). However, the variable Bank Indonesia Certificates Sharia (SBIS), FED Rate, and World Gold Price, they do not have signficant influence on the Indonesia Sharia Stock Index (ISSI). The results showed that Bank Indonesia Certificates Sharia (SBIS), BI Rate, Exchange Rates (Kurs), FED Rate, and World Gold Price had a significant simultaneous effect on the ISSI, and the result of determination coefficient adjusted R2 values of 35,2%.